1995
DOI: 10.1109/94.484310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physico-chemical degradation of epoxy resin on partial discharge behavior

Abstract: Epoxy resin coated electrode specimens were subjected to partial discharges (PD) in air at twice the discharge inception voltage for durations ranging to 5000 h. The PD behavior was 1070-9878/95/ $3.00 @ 1995 IEEE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…As already reported in the literature, in large disk-shaped voids, transition takes place from streamer mechanism to Townsend mechanism due to a conducting layer formed on the dielectric walls by discharge by-products [7][8][9][10][11]. However, an important point to note is that streamer discharges do not occur in submillimeter cavities, in the absence of the critical length required for formation of a streamer head [1].…”
Section: Introductionmentioning
confidence: 83%
“…As already reported in the literature, in large disk-shaped voids, transition takes place from streamer mechanism to Townsend mechanism due to a conducting layer formed on the dielectric walls by discharge by-products [7][8][9][10][11]. However, an important point to note is that streamer discharges do not occur in submillimeter cavities, in the absence of the critical length required for formation of a streamer head [1].…”
Section: Introductionmentioning
confidence: 83%
“…The deposition of liquid by-products has been reported by many authors, mainly for polyethylene [16][17][18][19][20] and epoxy [21][22][23][24][25]. Gamez-Garcia et al [26] showed that droplets were formed on the surface of XLPE only when an atmosphere containing water and carbon monoxide was present.…”
Section: Liquid By-productsmentioning
confidence: 99%
“…Hudon et al [21,24] studied the PD behavior in an 0.5 mm air gap between epoxy covered electrodes in an unvented test cell. Initially, they detected large amplitude discharges that they named spark-type.…”
Section: Pd Mechanism Pulse Shape and Opticalmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as a complement of overall aging condition evaluation based on traditionally physicochemical parameters, PD analysis with the development of electrical degradation is of great significance, especially for risk assessment and fault diagnosis. So far a lot of researches focus on the analysis of PD properties and corresponding degradation products, mainly applied for epoxy and XLPE, in which prominent achievements have been made [2][3][4][5][6]. However, there are few reports in regard to the degradation process of oil-paper insulation in power transformers.…”
Section: Introductionmentioning
confidence: 99%